High frequency of phylogenetically diverse reductive dehalogenase-homologous genes in deep subseafloor sedimentary metagenomes - Kawai, Mikihiko; Futagami, Taiki; Toyoda, Atsushi; Takaki, Yoshihiro; Nishi, Shinro; Hori, Sayaka; Arai, Wataru; Tsubouchi, Taishi; Morono, Yuki; Uchiyama, Ikuo; Itoh, Takehiko; Fujiyama, Asao; et al. (Frontiers in Microbiology, 2014)
Marine subsurface sediments on the Pacific margin harbor diverse microbial communities even at depths of several hundreds meters below the seafloor (mbsf) or more. Previous PCR-based molecular analysis showed the presence of diverse reductive dehalogenase gene (rdhA) homologs in marine subsurface sediment, suggesting that anaerobic respiration of organohalides is one of the possible energy-yielding pathways in the organic-rich sedimentary habitat. However, primer-independent molecular characterization of rdhA has remained to be demonstrated. Here, we studied the diversity and frequency of rdhA homologs by metagenomic analysis of five different depth horizons (0.8, 5.1, 18.6, 48.5, and 107.0 mbsf) at Site C9001 off the Shimokita Peninsula of Japan. From all metagenomic pools, remarkably diverse rdhA-homologous sequences, some of which are affiliated with novel clusters, were observed with high frequency. As a comparison, we also examined frequency of dissimilatory sulfite reductase genes (dsrAB), key functional genes for microbial sulfate reduction. The dsrAB were also widely observed in the metagenomic pools whereas the frequency of dsrAB genes was generally smaller than that of rdhA-homologous genes. The phylogenetic composition of rdhA-homologous genes was similar among the five depth horizons. Our metagenomic data revealed that subseafloor rdhA homologs are more diverse than previously identified from PCR-based molecular studies. Spatial distribution of similar rdhA homologs across wide depositional ages indicates that the heterotrophic metabolic processes mediated by the genes can be ecologically important, functioning in the organic-rich subseafloor sedimentary biosphere.